Design and Development of a Novel Transtibial Cycling Prosthesis. Issue 2 (April 2020) - Tiele, Akira; Soni-Sadar, Shivam; Rowbottom, Jack; Patel, Shilen; Mathewson, Edward; Pearson, Samuel; Hutchins, David; Head, John; Hutchins, Stephen
ABSTRACT: Introduction: This article describes the design methodology, creation, and testing of a bespoke transtibial prosthesis, manufactured in part using three-dimensional (3D) printing technology, to enable more effective transmission of dynamic pressure through pedals during cycling. Asymmetry in motion can occur during cycling between the affected and contralateral lower limb. This pilot study was devised to enable development of a prototype prosthesis using a flexible ankle joint design for people with transtibial lower-limb absence for use when participating in amateur sports cycling. Materials and Methods: Gait laboratory analysis and in-shoe plantar pressure measurement were used to simultaneously measure heel/ankle kinematics, plus pressure magnitude/distribution applied during cycling. A volunteer subject cycled on a static rig wearing either a standard unilateral transtibial prosthesis or a prototype prosthesis, which incorporated a simulated Achilles tendon. An able-bodied volunteer acted as a control. Results: The results indicate that cycling with the prototype prosthesis reduced bilateral ankle and heel kinematic misalignment by 64% and reduced unwanted pedal pressure during the cycling recovery phase from 60 N to 50 N. Conclusions: The use of 3D printing is a feasible option in the design and manufacture of lower-limb prostheses designed for cycling. Further research is needed to confirm this in a larger cohort of patients.